PENGARUH KOORDINASI MATA TANGAN DAN POWER OTOT LENGAN BAHU TERHADAP KEMAMPUAN PASSING BAWAH TEAM BOLA VOLI PUTRA SMK MUHAMMADIYAH 3 PEKANBARU - Gusfar Hidayatullah; Drs. Ramadi, M.Kes '; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this study was to determine the effect of hand-eye coordination and muscle power arm below the shoulder of the passing ability of men's volleyball team SMK Muhammadiyah 3 Pekanbaru. The type of study is a correlation study types. According Arikunto (2006: 273) argues that this research is a correlational study by comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. The population in this study were 7 students of class X, 6 students of class XI and XII grade 4 students. Data collection techniques in this study using total sampling for counting a sample that is not too large. Results of analysis showed that there are significant hand-eye coordination and muscle power arm below the shoulder of the passing ability of men's volleyball team SMK Muhammadiyah 3 Pekanbaru with r = (0.640)> rtabel = (0.497).Keywords: Wrist, Arm Shoulder Muscle Power, Passing, Volleyball.2PENGARUH KOORDINASI MATA TANGAN DAN POWER OTOT